Boosting Verbal Memory Capacity in Elementary School Students : A Face to Face Intervention Study - Nuha, Faza Izzuddin; Suharso, Puji Lestari (Universitas Pendidikan Mandalika, 2025)
This study aims to measure the effectiveness of non-technological working memory interventions in improving the verbal working memory capacity of a third-grade student, who experiences learning difficulties in reading comprehension and maintaining focus in class.The research employed a qualitative approach using a single-case reversal design (A1BA2) over 12 sessions. The intervention focused on enhancing D's phonological loop function through face-to-face, non-digital working memory training exercises, such as the odd one out and listening recall tasks. Data were collected through semi-structured interviews with parents and teachers, as well as non-participatory observations in both school and home environments. Data analysis involved comparing pre- and post-intervention performance to identify changes in working memory abilities. The findings indicate that this intervention can enhance verbal working memory capacity, supporting improvements in reading comprehension and focus. This suggests that non-technological, easily implementable interventions can provide a practical solution for enhancing cognitive abilities in children, particularly those from low socioeconomic backgrounds, with potential long-term benefits for academic performance.